Measurement and data analysis for engineering and science - Dunn, Patrick F.; Davis, Michael P. (CRC Press, Taylor & Francis Group, 2018)
These feature Measurement System Components, Assessing Measurement System Performance, Setting Signal Sampling Conditions, Analyzing Experimental Results, and Reporting Experimental Results. More practical examples, case studies, and a variety of homework problems have been added; and MATLAB and Simulink resources have been updated.